2013
DOI: 10.1371/journal.pone.0062874
|View full text |Cite|
|
Sign up to set email alerts
|

Assisted Knowledge Discovery for the Maintenance of Clinical Guidelines

Abstract: BackgroundImproving antibiotic prescribing practices is an important public-health priority given the widespread antimicrobial resistance. Establishing clinical practice guidelines is crucial to this effort, but their development is a complex task and their quality is directly related to the methodology and source of knowledge used.ObjectiveWe present the design and the evaluation of a tool (KART) that aims to facilitate the creation and maintenance of clinical practice guidelines based on information retrieva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The analyses of the classification precision according to the size (or type) of the document shows that there is no correlation between these two dimensions. While it might be counter-intuitive, several works have demonstrated that for classification tasks, the performance of abstracts are at least equivalent to full texts, when not better [29]. Yet, it could be relevant to explore the use of different classifiers for abstracts and for full texts.…”
Section: Classification Performance Per Category Document Size and Omentioning
confidence: 99%
“…The analyses of the classification precision according to the size (or type) of the document shows that there is no correlation between these two dimensions. While it might be counter-intuitive, several works have demonstrated that for classification tasks, the performance of abstracts are at least equivalent to full texts, when not better [29]. Yet, it could be relevant to explore the use of different classifiers for abstracts and for full texts.…”
Section: Classification Performance Per Category Document Size and Omentioning
confidence: 99%
“…environment will also need to change, with an infrastructure that supports CPG use (72), facilitates the development of consistent G4GAC, and accesses more electronic and computerized vehicles. Several innovations have been designed to automate continuous CPG frameworks, composed of decision support systems, a central patient database (e.g., EHR), a central medical knowledge base (e.g., peer-reviewed published literature), and an engine applying the knowledge base to the database (83)(84)(85)(86)(87). Diagnostic errors can result from a variety of cognitive issues and though managed superficially with CC, have been addressed with more advanced computational methods such as a semantic web framework composed of case-based fuzzy cognitive maps and Bayesian belief networks (88).…”
Section: Implementation Strategies and Tacticsmentioning
confidence: 99%
“…Computer-interpretable algorithm (96,97) Mobile device (98,99) Patient health records (83)(84)(85)(86)(87) Web-based (100)…”
Section: Electronic Formatsmentioning
confidence: 99%
“…Some other software tools focus on capturing the knowledge required to create CG recommendations [18]. Most of such approaches are markup-based tools such as GMT [19], DELT/A [ [20], Tallis [21], Stepper [22], GEM Cutter [23], and Uruz [24], [25].…”
Section: Related Workmentioning
confidence: 99%
“…Basically, medical processes are modeled using Business Process Management implementation (jBPM) and, given clinical data, a RETE-based rule engine is used for alerts and auditing. Still, some of the last trends in CG is the collaborative encoding [30], and the definition of a methodology and tools for the maintenance of CG [18].…”
Section: Related Workmentioning
confidence: 99%